Metrics in outpatient stewardship: Is more always better?. (July 2022) - Medvedeva, Natalia; Ha, David; Onguti, Sharon; Rosen, Emily; Mui, Emily; Pearce, Sean; Schneider, Alex; Chang, Amy; Hersh, Adam; Stenehjem, Eddie; Holubar, Marisa
Abstract : Background: Emerging evidence supports the use of billing data to identify stewardship targets in primary care. Standardizing an approach to antibiotic prescribing rate (APR) calculations could facilitate external benchmarking. Methods: Using methodology and an ICD-10 dictionary validated in urgent care clinics, 1 we created an expanded ICD-10 dictionary to incorporate additional ICD-10 codes from primary care associated with antibiotic prescriptions (Fig. 1 ). We then compared antibiotic prescribing rates using the urgent care and expanded dictionaries. We included all primary care visits from 2019 to 2020 and extracted ICD-10 codes and antibiotic order data. Using the urgent care and expanded ICD-10 dictionary, we classified each encounter by prescribing tier based on whether antibiotics are almost always (tier 1), sometimes (tier 2), or almost never (tier 3) indicated. For encounters with ICD-10s in multiple tiers, we chose the lowest tier. For multiple ICD-10 codes within the same tier, we chose the first extracted ICD-10 code. We calculated antibiotic prescribing rates as the proportion of encounters associated with ≥ 1 antibacterial prescription. This quality improvement project was deemed non–human subjects research by the Stanford Panel on Human Subjects in Medical Research. Results: The urgent care dictionary has 1, 400 ICD-10 codes. We added 1, 439 ICD-10 codes derived from primary care encounters to create the expanded ICD-10 dictionary (8.5% tier 1, 9.1% tier 2, and 82.4% tier 3) (Fig. 1 ). We identified 177, 531 encounters; 74% had ≥ 2 associated ICD-10 codes (Fig. 2 ). In total, 147, 085 encounters (82.9%) were classified into a tier using the urgent care dictionary. An additional 22, 039 encounters were classified with the expanded dictionary (Table 1 ). Most added encounters were tier 3 with low 0.7% APR (Tables 1 and 3 ). In total, 41, 473 (28.2%) encounters were classified differently depending on the ICD-10 dictionary used, most commonly changing from tier 3 to tier 2 without an increase in overall tier 2 antibiotic prescribing rate (Tables 2 and 3 ). Overall antibiotic prescribing rates were similar when using either the urgent care or expanded ICD-10 dictionary (Table 2 ). Conclusions: The expanded ICD-10 dictionary allowed for classification of more encounters in primary care; however, it did not meaningfully change antibiotic prescribing rates. Antibiotic prescribing rates were likely diluted by classifying more encounters without identifying an associated increase in antibiotic prescribing. A more sophisticated classification system may help to accommodate the diversity and volume of ICD-10 codes used in primary care. 1. Stenehjem E, et al. Clin Infect Dis 2020;70:1781–1787. Funding: None Disclosures: None